أليات الوقاية والردع لجرائم الصفقات العمومية في التشريع الجزائري - قتال, الطيب (University of Eloued جامعة الوادي, 2022)
تعتبر الصفقات العمومية تقنية تعتمد عليها الهيئات الإدارية ,من أجل تنفيذ مشاريعها التنموية, فهي بذلك تعد المجال الخصب للفساد بكل صوره لإرتباطها بمجال المال والأعمال وتفاديا لإهدار المال العام في مجال الصفقات العمومية, قام المشرع الجزائري بتعديل القوانين المتعلقة بها كلما أتيحت له الفرصة لإحاطتها بنصوص صارمة وآليات وقائية فعالة كالتدابير المرتبطة بالموظف لاسيما الكفاءة والنزاهة لتولي الوظائف العامة, وضرورة التصريح بممتلكاتهم حتى يكونوا بعدين كل البعد عن الصفقات المشبوهة, ومن أجل حماية الصفقات العمومية من الجرائم المتصلة بها والتي تمس بالمال العام ونزاهة الوظيفة العمومية,إبتكر المشرع آليات ردعية وعقابية في كل من قانون الوقاية من الفساد ومكافحته وقانون الإجراءات الجزائية والقوانين ذات الصلة, من خلال الكشف عن أساليب خاصة منها الضبطية القضائية وأعطى لها سلطة التحري دون المماس بحرمة الحياة الشخصية المنصوص عليها دستوريا. كما فعل دور المؤسسات المالية, بغية التعريف والكشف عن مرتكبي جرائم الصفقات العمومية, حيث خص مرتكبيها بجزاءات ونصوص عقابية سواء للشخص الطبيعي أو المعنوي. وبالتالي كل هذه الآليات الوقائية والردعية التي أتى بها المشرع الجزائري تهدف إلى حماية المال العام والمحافظة على الإقتصاد الوطني من الجرائم المترصد بها في مجال الصفقات العمومية إلا أن فعاليتها تبقى غير كافية لإفتقارها للصرامة في تطبيق الردع والإستقلالية في المهام والوظائف, نظرا لتعدد القطاعات في مختلف المجالات وإزدياد جرائم الصفقات العمومية التي تنخر الإقتصاد الوطني وتشكل نزيف للمال العام Public transactions are considered a technique on which administrative bodies rely, in order to implement their development projects. Thus, they are the fertile field for corruption in all its forms, as they are related to the field of finance and business. And effective preventive mechanisms such as measures related to the employee, especially the efficiency and integrity to assume public functions, and the need to declare their properties so that they are far away from suspicious transactions, and in order to protect public transactions from related crimes that affect public money and the integrity of the public office, the legislator devised deterrent and punitive mechanisms in each From the Law on Prevention and Combating Corruption and the Law of Criminal Procedures and related laws, by revealing special methods, including judicial police, and giving them the authority to investigate without prejudice to the sanctity of personal life stipulated in the constitution. He also did the role of financial institutions, with the aim of identifying and revealing the perpetrators of the crimes of public transactions, as he singled out their perpetrators with penalties and punitive texts, whether for a natural or legal person. Consequently, all these preventive and deterrent mechanisms brought by the Algerian legislator aim to protect public money and preserve the national economy from the crimes that are lurking in the field of public deals. And the increase in crimes of public deals that corrode the national economy and constitute a drain on public money.
Preventive and deterrence mechanisms for offences against P ublic T ransactions in Algerian L egislation
مقال
Keywords: الصفقات العمومية؛ الآليات؛ المشرع الجزائري؛ الوقاية؛ الردع؛ جرائم؛ الإختصاص؛ الموظف؛ المال؛ الإقتصاد الوطني; public deals; Mechanisms; prevention; deterrence; employee.